A QUALITATIVE STUDY OF EMPLOYEE PERCEPTION ON PERFORMANCE APPRAISAL SYSTEM AT MAIN BRANCH OF BNI 46 MANADO - Karu, Sharon C.C.A; Lapian, S.L.H.V Joyce; Tielung, Maria V.J (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: The condition of an organization’s being effective is mainly dependent on its Human Resources Management. Performance Appraisal is important system that usually takes the form in periodic that works performance is evaluated, not only from their work responsibilities but employee behavior is evaluated too. The purpose of this study is focused on employee perception on performance appraisal and the implications at Main Branch of BNI 46 Manado. Data collected from 10 respondents at Main Branch of BNI 46 Manado that had been appraised previously. Types of data in this research used primary data and secondary data. This study method used case study (qualitative) because it is designed to get more understanding with the performance appraisal system at Main Branch of BNI 46 Manado, through employee to answer the questions that needed (depth-interview). This research found that based on employee perception the performance appraisal system that implemented at Main Branch of BNI 46 Manado, overall is good but sometimes employee feel the appraisal system not objective. The characteristics that assessed are based on each units. This research suggest to company to allow the employee to give feedback directly to supervisor, more transparent and agreement.Keywords: human resource management, employee perception, performance appraisal system